Working with Microsoft Access 2.0 - Blissmer, Robert H.; Alden, Roland H. (Boston : Houghton Mifflin, 1995)
Introducing Access. Queries and tables. Working with Access.
Keywords: Computer; Microsoft Windows; Microsoft Access; Database management; Microsoft Windows (Computer file); Database management; Microsoft Access (Computer file)